THE INFLUENCE OF DIFFERENT AGROCHEMICALS FOLIAR SPRAYS ON POSTHARVESTFRUIT QUALITY OF NAVEL ORANGE - Kassem, H. A.; Marzouk, H. A.; Abo-Elmagd, A. EL-Kobbia (Emirates Journal of Food and Agriculture, 2011)
The present investigation was carried out during the two successive growing seasons of 2003 and 2004 on Washington Navel orange trees grown at El-Tarh region, El-Behera Governorate, in order to study the effect of spraying orange trees with different agrochemicals on fruit quality. For the present study, 96 trees were selected as uniform as possible and divided into two groups. The first group was subjected to the foliage treatments when the fruit reached pea size (5mm in diameter) and the second at marble size (15mm in diameter). Fruit weight was significantly increased in both seasons by spraying 2,4- D + boric acid at the pea or marble stages. In addition, spraying 2,4-D + boric acid at the marble stage only increased fruit length .Vitamin C content was not affected by all sprays at the pea stage, whereas it was significantly increased in the first season by spraying 2,4-D, 2,4-D + calcium chloride, 2,4-D+ calcium acetate, urea or boric acid alone at the marble stage. In the second season, fruit acidity was increased by spraying boric acid at both pea and marble stage, whereas, it was decreased by spraying 2,4-D + calcium chloride ( pea stage) and 2,4-D + boric acid (marble stage). Spraying 2,4-D + calcium super phosphate at pea or marble stage significantly increased TSS percent. In addition, all treatments enhanced fruit color in both pea and marble stages over the control, especially, treatments that included foliar spray of 2,4-D. In general, most 2,4-D sprays combined with other compounds had significant influence on fruit quality characteristics.